2020
DOI: 10.1177/1060028020960037
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulant for the Treatment of VTE in Cancer Patients: A Systematic Review and Meta-analysis

Abstract: Background: Recent clinical guidelines suggest direct oral anticoagulants (DOACs) as treatment for cancer-associated thrombosis (CAT), but the strength of such recommendations was not clear. Newly released trials add uncertainties to the benefit and risk assessment between DOACs and conventional therapy (low-molecular-weight heparin [LMWH] or vitamin K antagonists [VKAs]). Objective: To evaluate the efficacy and safety of DOACs in patients with CAT, as compared with LMWH and VKAs. Methods: PubMed, EMBASE, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…At the time the search was ended (October 6, 2020), 46 records were identified, of which 26 were discarded on title and abstract ( n = 24) or full‐text ( n = 2). The 20 remaining meta‐analyses were published in nonpredatory peer‐reviewed journals: five studies pooled the data of two RCTs, 6‐10 four studies pooled the data of three RCTs, 11‐14 and 11 studies pooled the data of four RCTs 15‐25 . The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time the search was ended (October 6, 2020), 46 records were identified, of which 26 were discarded on title and abstract ( n = 24) or full‐text ( n = 2). The 20 remaining meta‐analyses were published in nonpredatory peer‐reviewed journals: five studies pooled the data of two RCTs, 6‐10 four studies pooled the data of three RCTs, 11‐14 and 11 studies pooled the data of four RCTs 15‐25 . The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 20 remaining meta-analyses were published in nonpredatory peer-reviewed journals: five studies pooled the data of two RCTs, 6-10 four studies pooled the data of three RCTs, [11][12][13][14] and 11 studies pooled the data of four RCTs. [15][16][17][18][19][20][21][22][23][24][25] The main characteristics of the 20 meta-analyses are described in Table 1 and the results of the 20 meta-analyses for efficacy and safety endpoint are shown Figure 1. Within each category of meta-analysis (two, three, or 4 RCTs), the results were similar regarding the risks of VTE recurrence (differences in pooled relative…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…In recent years, with respect to DOACs vs LMWH, besides SELECT-D trial [ 37 ], six meta-analyses indicated that DOACs were more efficacious in the treatment of cancer-associated VTE with an increase of bleeding risk, compared with LMWH [ 11 , 20 , 38 41 ], whereas a retrospective study [ 7 ] and another five meta-analyses [ 10 , 15 , 16 , 42 , 43 ] indicated that DOACs were more efficacious with a comparable bleeding risk, compared with LMWH. In the ADAM VTE trial, major bleeding and VTE recurrence rates were both lower in cancer patients with VTE receiving oral apixaban than those receiving dalteparin [ 44 ].…”
Section: Comparison Among Different Therapeutic Anticoagulant Agentsmentioning
confidence: 99%
“…With regard to DOACs vs VKA in recent years, one retrospective study [ 7 ] and two meta-analyses [ 10 , 42 ] reported that DOACs were more efficacious in the treatment of cancer-associated VTE with similar bleeding risk compared to VKA, whereas another two meta-analyses [ 11 , 38 ] indicated that DOACs were more efficacious with a decrease of bleeding risk, compared to VKA. Besides, the Hokusai-VTE trial reported that DOAC (edoxaban) was as effective as VKA (warfarin) for the treatment of patients with cancer-associated VTE with less bleeding risk [ 48 ].…”
Section: Comparison Among Different Therapeutic Anticoagulant Agentsmentioning
confidence: 99%
See 1 more Smart Citation